2022
DOI: 10.1139/cjpp-2022-0072
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen sensor of the heart

Abstract: How oxygen is sensed by the heart and what mechanisms mediate its sensing remain poorly understood. As recent reports show that low PO2 levels are detected by the cardiomyocytes in a few seconds, the rapid and short applications of low levels of oxygen (acute hypoxia), which avoid multiple effects of chronic hypoxia, may be used to probe the oxygen-sensing pathway of the heart. Here, we explored the oxygen-sensing pathway, focusing primarily on cellular surface membrane proteins that were first exposed to low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…The results of GSVA may explain some of the clinical manifestations of stress cardiomyopathy (Figure 3D), such as the upregulation of the ESTROGEN RESPONSE EARLY function, thus suggesting that sex influences stress cardiomyopathy [24]. Interestingly, the upregulation of HEME METABOLISM and GLYCOLYSIS suggested that myocardial hypoxia and increased peripheral myocardium metabolism due to stress cardiomyopathy do indeed occur [29]. The upregulation of immune-related functions (IL2 STAT5 SIGNALING) and coagulation-related functions (COAGULATION) suggested that the belief that stress cardiomyopathy is self-limiting may be inaccurate.…”
Section: Discussionmentioning
confidence: 95%
“…The results of GSVA may explain some of the clinical manifestations of stress cardiomyopathy (Figure 3D), such as the upregulation of the ESTROGEN RESPONSE EARLY function, thus suggesting that sex influences stress cardiomyopathy [24]. Interestingly, the upregulation of HEME METABOLISM and GLYCOLYSIS suggested that myocardial hypoxia and increased peripheral myocardium metabolism due to stress cardiomyopathy do indeed occur [29]. The upregulation of immune-related functions (IL2 STAT5 SIGNALING) and coagulation-related functions (COAGULATION) suggested that the belief that stress cardiomyopathy is self-limiting may be inaccurate.…”
Section: Discussionmentioning
confidence: 95%